Newspaper coverage on solidarity and personal responsibility in the COVID-19 pandemic: A content analysis from Germany and German-speaking Switzerland - Bettina M. Zimmermann; Alena Buyx; Stuart McLennan (Elsevier, 2023)
Solidarity and personal responsibility have been repeatedly called upon during the COVID-19 pandemic. This study quantifies and contextualizes the use of these terms in newspaper coverage in Germany and German-speaking Switzerland based on n = 640 articles from six functionally equivalent newspapers. The term solidarity in the context of the COVID-19 pandemic was mentioned in 541/640 articles (84.5%) and was primarily used during phases with high death rates and comparatively stringent policies in place, supporting the idea that solidarity was used to explain restrictive measures to the population and motivate people to comply with these measures. German newspapers published more articles on solidarity than Swiss-German newspapers, consistent with more stringent COVID-19 policies in Germany. Personal responsibility was mentioned in 133/640 articles (20.8%), meaning that the term was less frequently discussed than solidarity. Articles covering personal responsibility included more negative evaluations during phases of high infection rates as compared to phases of low infection rates. Findings indicate that the two terms were, at least to some extent, used in newspaper reporting to contextualize and justify COVID-19 policy during phases of high infection rates. Moreover, the term solidarity was used in a high variety of different contexts and the inherent limits of solidarity were rarely mentioned. Policymakers and journalists need to take this into account for future crises to not jeopardize the positive effects of solidarity.